Representation of Radiation Oncologists on National Comprehensive Cancer Network Guideline Committees - Bismarck C. Odei, MD; Temitope Agabalogun, MD; Erika Bello-Pardo, BS; Christina Huang, MD, MS; Daniel Vanderbilt, MD, PhD; Seyi Omeh, MD, MPH; Benjamin Sterling; Fumiko Chino, MD (Advances in Radiation Oncology)
Purpose: The National Comprehensive Cancer Network (NCCN) guideline committees (GCs) play a vital role in defining the standard of care for cancer management. Equitable specialty representation is crucial for unbiased recommendations and perspectives. This study examines the specialty and leadership representation on NCCN GCs, with a focus on radiation oncologists (ROs). Methods and Materials: This cross-sectional observational study evaluated committee member characteristics on NCCN treatment GCs available in 2020 and subset of committees with guidelines containing category 1 or 2A radiation therapy recommendations. Collected data included member characteristics and committee roles. Interspecialty variance was evaluated via χ2 tests. Results: A total of 1768 NCCN committee members were identified, representing 54 NCCN GCs with a median committee size of 33 (range, 22-38). Among all members: 47.6% were medical oncologists (MOs), 20.9% were surgical oncologists (SOs), and 8.9% were RO; 22.6% were other specialists. Women accounted for 37.6% (316/841) of MO, 34.2%(54/158) of RO and 22.8% (84/369) of SO members (P < .001). RO representation varied based on disease site (2.4%-29.9%; 15 individual committees had no RO representation) and in leadership roles (3% chairs, 23% vice chairs). On 38 committees with guidelines containing category 1 or 2A radiation therapy recommendations, the pattern of low representation persisted (8.4%). Although 39% of individuals on all committees were women, only 23% of committee chairs were women (P = .048). Conclusion: There is low representation of ROs on NCCN GCs and in leadership roles, which may limit the discussion during guideline development and negatively impact the diversity of perspectives in management recommendations.